2012
DOI: 10.24846/v21i3y201201
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Specific AR Capabilities on the Learning Effectiveness and Efficiency

Abstract: Augmented reality (AR) is a promising technology for improving the applicative and comprehension skills of students. The ARiSE project developed an Augmented Reality Teaching Platform (ARTP) for secondary schools. A Chemistry learning scenario was implemented that is based on the interaction paradigm "building with guidance". This study aims at assessing the extent to which specific capabilities of the ARTP support the understanding of Chemistry concepts as well as their contribution to the perceived utility. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 5 publications
2
32
0
2
Order By: Relevance
“…Namely, learning from systems that present relevant materials (e.g., images, texts, videos) in a well integrated and organized form can avoid incidental cognitive load and benefit students by improving their learning performance (Chiang et al, 2014). Findings in the literature have also reported that when AR applications are well designed, better learning can be achieved with less cognitive effort (Di Serio et al, 2012;Iordache et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Namely, learning from systems that present relevant materials (e.g., images, texts, videos) in a well integrated and organized form can avoid incidental cognitive load and benefit students by improving their learning performance (Chiang et al, 2014). Findings in the literature have also reported that when AR applications are well designed, better learning can be achieved with less cognitive effort (Di Serio et al, 2012;Iordache et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Küçük et al (2016) also stated that students who worked with AR applications reported to experience less cognitive load than students who studied anatomy using a textbook (Küçük et al, 2016). Other studies also found that, when AR applications are well designed, less cognitive effort can be achieved when using these applications for the study of anatomy (Iordache et al, 2012;Di Serio et al, 2013).…”
Section: Secondary Outcomes In Light Of the Literaturementioning
confidence: 99%
“…However, working with AR has also been suggested to possibly reduce cognitive load (Küçük et al, 2016). This can possibly be explained by findings in literature which report that when AR applications are well-designed, better learning can be achieved with less cognitive load (Iordache et al, 2012;Di Serio et al, 2013). Such well-designed AR application adheres to the spatial and the temporal continuity principles of the cognitive theory of multimedia learning (Mayer, 2009;Wilson, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The growth of Internet and use of digital multimedia objects offered practically limitless possibilities for implementing steganographic applications. In [6] the authors present the importance of using various techniques (steganography included) for improving the specific capabilities of an Augmented Reality Teaching Platform. Former analogical steganographic techniques dedicated to security applications found their equivalent in digital steganography [3].In networking, steganography can be used in order to implement QoS like mechanisms or to increase the security and privacy of the network data package [8], [9], [14].…”
Section: Related Workmentioning
confidence: 99%